Os créditos de carbono e a indústria cerâmica no Ceará - Sales, Juscelino Chaves (2011)
We can say that the way the man is acting we are heading for an ecological apocalypse. The planet Earth is sick where the Brotherhood Campaign of the Catholic Church in Brazil this year says in their motto "Creation groans in travail" (RM8, 28). Recently completed In Manaus the Amazon state of the first World Forum on Sustainability, attended by several researchers and officials discussing sustainable development. The potteries were known as the factories of ceramic products are considered highly polluting, or harm to the environment through the emission of gases that cause global warming through its furnaces that release CO2 mainly by burning fire wood. This paper shows how some industries that produce mainly red ceramic blocks in Ceará managed to earn carbon credits for changing the wood fuel used by others in their ovens, as the bark of chestnut quenga coconut, powder mill.